THE ROLE OF ISLAMIC BANKING IN INCREASING THE POTENTIAL OF TRADITIONAL MARKETS REVIEWED FROM AN ISLAMIC PERSPECTIVE - Bagas Taqwa; Evy Oktaviani Fauzi; Astuti (Fakultas Ekonomi Universitas IBA Palembang, 2025)
In the National Development carried out by the Indonesian Nation which is one way to achieve development goals to create community welfare based on the Constitution and the fifth principle of Pancasila. This study was conducted with the aim of understanding the role of banking in increasing the potential of traditional markets in an Islamic perspective. This study uses a descriptive method with a qualitative approach. The data source for this study uses primary data and secondary data. The data collection technique used is interviews. The results of this study are Based on interviews conducted by researchers with morning market actors in the Cirebon City Prosecutor's Office, especially traders who utilize banking financial services, there has been an increase in adequate results or income. With the increase in capital from bank loans, traders are able to increase the quantity of merchandise and types of goods traded. This shows that banking companies have a great contribution in increasing the potential of traditional markets in the Cirebon City Prosecutor's Office Morning Market